Enhancing the observability of the Efimov effect in ultracold atomic gas mixtures - D’Incao, J. P.; Esry, B. D. (My University, 2006)
We discuss the prospects for observing the characteristic features of the Efimov effect in a two-component ultracold atomic gas near an interspecies Feshbach resonance. In the ultracold regime, the Efimov effect is expected to be manifested in the three-body collision rates through the appearance of series of minima or maxima as a function of the two-body s-wave scattering length a. Here, we propose the observation of this Efimov physics through measurements of the inelastic three-body rate constants near a Feshbach resonance. Our analysis suggests that boson-fermion mixtures, where the bosons are much heavier than the fermions, are the most favorable system to observe such features.